Fine-tuning the dose of recombinant human follicle-stimulating hormone alfa to individualize treatment in ovulation induction and ovarian stimulation cycles: a real-world database analysis - Martini, Anne E.; Beall, Stephanie; Ball, G David; Hayward, Brooke; D’Hooghe, Thomas; Mahony, Mary C.; Collares, Fabricio; Catherino, Allison B. (Frontiers in Endocrinology, 2023)
Introduction: Fine-tuning of injectable gonadotropin doses during ovulation induction (OI) or ovarian stimulation (OS) treatment cycles with the aim of using doses low enough to minimize the risk of excessive ovarian response while maintaining optimal efficacy may be facilitated by using an adjustable-dose pen injector. We examined the incidence and magnitude of individualized gonadotropin dose adjustments made during cycles of OI or OS, followed by either timed intercourse or intrauterine insemination, with or without oral medications, and assessed the relationship between patient characteristics and dosing changes using real-world evidence. Methods: This was an observational, retrospective cohort study using electronic medical records from a large US database of fertility centers. Data from patients who had undergone a first recombinant human follicle stimulating hormone alfa (r-hFSH-alfa/follitropin alfa) treated OI/OS cycle followed by timed intercourse or intrauterine insemination between 2015 and 2016 were included. Percentages of OI/OS cycles involving r-hFSH-alfa dose adjustments (in increments of ±12.5 IU or greater) with or without oral medications (clomiphene citrate or letrozole) were analyzed. Results: Of 2,832 OI/OS cycles involving r-hFSH-alfa administration, 74.6% included combination treatment with orals; 25.4% involved r-hFSH-alfa alone. As expected, the starting dose of r-hFSH-alfa was lower for cycles that used r-hFSH-alfa with orals than r-hFSH-alfa only cycles (mean [SD]: 74.2 [39.31] vs 139.3 [115.10] IU). Dose changes occurred in 13.7% of r-hFSH-alfa with orals versus 43.9% of r-hFSH-alfa only cycles. Dose adjustment magnitudes ranged from ±12.5 IU to ±450 IU. The smallest adjustment magnitudes (±12.5 IU and ±25 IU) were used frequently and more often for dose increases than for dose decreases. For r-hFSH-alfa with orals and r-hFSH-alfa only cycles, the smallest adjustments were used in 53.5% and 64.5% of cycles with dose increases and in 35.7% and 46.8% of cycles with dose decreases, respectively. Discussion: In OI/OS cycles followed by timed intercourse or intrauterine insemination, r-hFSH-alfa dose adjustments were frequent. In cycles that included orals, r-hFSH-alfa starting doses were lower and dose changes were fewer than with r-hFSH-alfa alone. Smaller dose adjustments facilitate individualized treatment with the goal of reducing the risks of multiple gestation, cycle cancellation, and ovarian hyperstimulation syndrome.